A comprehensive pore structure study of the Bakken Shale with SANS, N2 adsorption and mercury intrusion - Kouqi Liu; Mehdi Ostadhassan; Liangwei Sun; Jie Zou; Yujie Yuan; Thomas Gentzis; Yuxiang Zhang; Humberto Carvajal-Ortiz; Reza Rezaee (Fuel, 2019)
Small angle neutron scattering (SANS) analysis was performed on six Bakken Shale samples with different maturities to reveal the complexities in the pore structure. Pore size distribution (PSD), porosity and specific surface area (SSA) were calculated from SANS data via the Polydisperse Spherical Pore (PDSP) model and compared with the data from N2 adsorption and mercury intrusion. The results showed that the Bakken samples have a very small porosity value (less than 1%) and a very larger specific surface area (larger than 180995 cm−1) in the measuring pore size range (pore diameter: 1–200 nm). SANS and N2 adsorption can detect pores in the similar size range (2–200 nm). The SSA measured by SANS and mercury intrusion was found larger than the one detected by N2 adsorption. Pore structure information that is obtained from SANS, N2 adsorption, and mercury intrusion methods exhibited a fractal and multifractal behavior. Moreover, the pore size distribution that is calculated from SANS data was the most heterogeneous. Finally, the effects of rock composition on pore structures demonstrated that organic matter hosts some isolated pores while clay minerals do not host a large quantity of pores that are either connected or isolated.
Keywords: Bakken shale; Mercury intrusion; N adsorption; Pore structure; Rock-Eval pyrolysis; SANS